Bacterial and Fungal Loads in Raw Sea Foods, Fruits and Vegetables collected from Dhaka, Bangladesh and the Effect of Heat on its Growth - Feroz, Farahnaaz; Mori, Miho; Sakagami, Yoshikazu (Bangladesh Journal of Microbiology, 2018)
Foods, fruits and vegetables are essential foodstuffs which can also serve as a major source of bacterial and fungal transmission. Mishandling of fruits, vegetables and foods during storage, transport, inadequate preparation and unsanitary conditions during processing have led to the spread of foodborne diseases worldwide, especially in Bangladesh. A total of 51 samples of fruits (n=16), vegetables (n=16) and seafoods (n=19) were studied for the determination of bacterial and fungal loads and assessment of heat effect on microbial growth. All categories of 51 samples showed initial bacterial counts ranging from 4 X 103 - 7 X 106 cfu/g, and fungal counts ranging from 103 - 106 cfu/g. Fruits, vegetables and seafood samples showed bacterial counts ranging from 4 X 103 - 4 X 105, 5 X 104 - 1 X 106, and 3 X 104 - 7 X 106, and fungal counts ranging from 6 X 103 - 1 X 105/g, 9 X 104 - 7 X 105/g, and 1 X 103 1 X 106/g, respectively. Just after microbiological analyses, all different categories of samples were heat treated at 60OC for three intervals viz 30 minutes, 1 hour and finally 2 hours. Heating at 60OC showed efficiency in reducing bacterial and fungal growth in the samples studied with log reductions not venturing below the 1.00 mark and various samples with log reductions more than 5.00. Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 23-28